2022
DOI: 10.1161/atvbaha.122.315499
|View full text |Cite
|
Sign up to set email alerts
|

Leu22_Leu23 Duplication at the Signal Peptide of PCSK9 Promotes Intracellular Degradation of LDLr and Autosomal Dominant Hypercholesterolemia

Abstract: Background: PCSK9 (Proprotein convertase subtilisin/kexin type 9) regulates LDL-C (low-density lipoprotein cholesterol) metabolism by targeting LDLr (LDL receptor) for lysosomal degradation. PCSK9 gain-of-function variants cause autosomal dominant hypercholesterolemia by reducing LDLr levels, the D374Y variant being the most severe, while loss-of-function variants are associated with low LDL-C levels. Gain-of-function and loss-of-function activities have also been attributed to variants occurring i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In a study conducted on 1,745 apparently healthy individuals, plasma PCSK9 levels were significantly lower in individuals carrying a leucine insertion in exon 1 of the PCSK9 gene (Awan et al, 2013). Moreover, the insertion of two leucines in the signal peptide has been reported in a family with familial combined hyperlipidemia and two patients with FH (Abifadel et al, 2008) and in vitro studies have shown that it causes a reduction in the secretion of the mature form of PCSK9 compared to the wild type PCSK9 (Benito-Vicente et al, 2022). However, these variations might not alone explain the very low levels of PCSK9 observed in homozygous carriers of the LPL variant in our study.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In a study conducted on 1,745 apparently healthy individuals, plasma PCSK9 levels were significantly lower in individuals carrying a leucine insertion in exon 1 of the PCSK9 gene (Awan et al, 2013). Moreover, the insertion of two leucines in the signal peptide has been reported in a family with familial combined hyperlipidemia and two patients with FH (Abifadel et al, 2008) and in vitro studies have shown that it causes a reduction in the secretion of the mature form of PCSK9 compared to the wild type PCSK9 (Benito-Vicente et al, 2022). However, these variations might not alone explain the very low levels of PCSK9 observed in homozygous carriers of the LPL variant in our study.…”
Section: Discussionmentioning
confidence: 96%
“…These polymorphisms occur in the signal peptide region of the PCSK9 protein and are characterized by the insertion of one or two leucines into a stretch of nine leucines (Chen et al, 2005;Yue et al, 2006;Abifadel et al, 2008). They might lead to a structural change in the signal peptide causing an impairment in its cleavage and processing in the endoplasmic reticulum (Yue et al, 2006;Pisciotta et al, 2012;Benito-Vicente et al, 2022). In a study conducted on 1,745 apparently healthy individuals, plasma PCSK9 levels were significantly lower in individuals carrying a leucine insertion in exon 1 of the PCSK9 gene (Awan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation